Micropropagation of Dysophylla myosuroides (Roth.) Benth. In. Wall. through leaf culture - Savithramma, N.; Ankanna, S.; Prabha, Beena; Sasikala, A. (Research in Biotechnology, 2012)
A method was developed through leaf as explant of Dysophylla myosuroides (Roth.) Benth. for multiple shoot regeneration. The effect of Auxins (IAA, NAA, IBA) and Cytokinins (BA) were studied on shoot regeneration in clulture. On MS half strength medium light green compact calli were formed with 0.1 mg l-1 NAA. The cultures produced 62.57 + 0.04 shoots on half strength medium with 0.5 mg l-1 BA and 0.01 mg l-1 NAA and also maximum mean length (0.52 + 0.02) of shoots were achieved. In vitro produced shoots rooted on half strength MS medium with 1 mg l-1 IBA. The in vitro regenerated plantlets were successfully acclimatized in paper cups containing vermiculate, then transferred to green house. Hardened plants were transplanted in to sand and soil (1 : 1).